2017
DOI: 10.1177/0004867417707818
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need for professional mental health care among adolescents with high psychological distress

Abstract: A concerning proportion of adolescents have untreated high psychological distress with wholly unmet mental health needs. This group is rendered particularly vulnerable by low rates of access to non-professional sources of help and low engagement in self-management strategies. Further research is needed to support this vulnerable group to access needed professional mental health help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 22 publications
8
36
0
2
Order By: Relevance
“…As a result, they might prefer to manage their mental health problem alone perhaps utilizing both positive and negative strategies such as problem-solving [72], substance uses, and isolation [73] as examples. The present finding supports past studies reporting a major barrier to receiving formal mental health service among university students with mild to moderate depression and anxiety is preferring to self-medicate [74,75]. The fourth barrier identified in the present study is denying mental health problems.…”
Section: Discussionsupporting
confidence: 90%
“…As a result, they might prefer to manage their mental health problem alone perhaps utilizing both positive and negative strategies such as problem-solving [72], substance uses, and isolation [73] as examples. The present finding supports past studies reporting a major barrier to receiving formal mental health service among university students with mild to moderate depression and anxiety is preferring to self-medicate [74,75]. The fourth barrier identified in the present study is denying mental health problems.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that majority of the students receive mental health help from friends, family, relatives, religious leaders, and traditional healers [38], which is also common practice in the general population of Ethiopia [78]. The present finding is also supported by previous studies, where informal sources of mental health care reported by college students as a reason for not to receive mental health services in their university [71,79].…”
Section: Discussionsupporting
confidence: 84%
“…As a result, they may prefer to manage their mental health problem using a healthy coping mechanism like problem-solving [69] or using unhealthy coping strategies such as substance use and isolation [70]. The present finding supports the past studies reporting a major barrier for receiving formal mental health service among university students with mild to moderate depression and anxiety was preferring to selfmedication [71,72].…”
Section: Discussionsupporting
confidence: 83%